2015
DOI: 10.1016/j.envint.2015.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Environmental exposure to lithium during pregnancy and fetal size: A longitudinal study in the Argentinean Andes

Abstract: Lithium exposure through drinking water was associated with impaired fetal size and this seemed to be initiated in early gestation. Further studies are warranted to confirm causality and to understand the mechanisms. If confirmed, these findings have public health relevance and emphasize the need for more data on lithium concentrations in drinking water, including bottled water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 53 publications
(59 reference statements)
2
49
0
1
Order By: Relevance
“…The studied population co-exposed to boron and lithium at the same time. The authors reported an inverse association also between lithium exposure during pregnancy and fetal size in their earlier published study at the same sampling area [16]. On the other hand, the study area is located 3180-4070 m above the sea level.…”
Section: The Results Of the Epidemiological Study In Argentinamentioning
confidence: 88%
“…The studied population co-exposed to boron and lithium at the same time. The authors reported an inverse association also between lithium exposure during pregnancy and fetal size in their earlier published study at the same sampling area [16]. On the other hand, the study area is located 3180-4070 m above the sea level.…”
Section: The Results Of the Epidemiological Study In Argentinamentioning
confidence: 88%
“…Thus, lithium could cause memory disorders and seizures (Bartha et al, ), neurotoxicity (Ahmad et al, ; Aral & Vecchio‐Sadus, ) and epilepsy (Xiao et al, ). Alternatively, lithium can exert this disturbance by initiating cellular hypothyroidism (Bolaris, Margarity, & Valcana, ), reducing the birth weight (Harari et al, ), decreasing the energy balance (Brietzke, Stabellini, Grassi‐Oliveira, & Lafer, ), increasing cytokine imbalances (Grignon & Bruguerolle, ) and activating DNA fragmentation in cerebrum of rats (Shao, Young, & Wang, ). In addition, hypothyroidism impairs development of the monoaminergic system (Ahmed, Abdel‐Latif, Mahdi, et al, ; Ibrahim, Tousson, El‐Masry, Arafa, & Akela, ; Tousson, Ibrahim, Arafa, & Akela, ), causing a pathophysiological status (Van Herck et al, ) and neurodevelopmental disorders (Andersen et al, ; Gilbert, Goodman, Gomez, Johnstone, & Ramos, ; O'Shaughnessy et al, ; Salazar, Cisternas, Martinez, & Inestrosa, ; Thompson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Poels, Bijma, Galbally, and Bergink (2018) noticed the coordination between first-trimester lithium exposure and an increased hazard of congenital malformations. Indeed, lithium exposure early in pregnancy might be increased the risk of Ebstein's anomaly (an obstruction defect in the right ventricular outflow tract) in infants (Patorno et al, 2017), intrauterine growth restriction (Harari et al, 2015), teratogenic insults (Giles & Bannigan, 2006;Klug, Collins, Nagao, Merker, & Neubert, 1992;Marathe & Thomas, 1986) and cyanosis, lethargy, depressed neurological status, hypotonia and poor suck reflexes (Wood, 2012). Furthermore, exposure of neonatal rats to 85, 255 or 255 + 127 μg LiCl causes a toxic effect during development (Menshanov et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that serum boron concentrations above 80 µg/L were inversely associated with birth length and weight. However, it remains open whether boron was in fact the causative agent in this case, because at the same time, also lithium exposure through the drinking water appeared associated with impaired foetal size (Harari et al 2015). In addition, the high-altitude effect must be considered.…”
Section: Focus Of Toxicological Researchmentioning
confidence: 93%